Cell death‐inducing properties of selected dendrimers against different breast cancer and leukemia cell lines. Issue 11 (11th August 2020) - Baecker, Daniel; Kapp, Timo; Schumacher, Petra; Gust, Ronald; Kircher, Brigitte
Abstract: Dendrimers represent an opportunity for targeted drug delivery into tumor cells. This is facilitated, for example, by loading of dendrimers with anticancer compounds. However, to assess the effects caused by such conjugates, knowledge of the cytotoxicity of the dendrimers themselves is necessary. The poly(amido amine)‐derived dendrimers G1 (Phe)6, G1 (Dan)3, and G2 were selected due to their different numbers of free amino groups and the poly(propylene imine) (PPI) dendrimer PPI‐G3 served as a reference. The compounds were evaluated for cell‐death induction using breast cancer (MCF‐7, MDA‐MB‐231) and leukemia (LAMA‐84, K562, SD‐1, SUP‐B15) cell lines. The compounds exhibited concentration‐dependent effects in the low micromolar range against the mammary carcinoma cells. A dependency on the generation, and particularly on the type of dendrimer, was deduced while the quantity of the free amino groups was subsidiary. G2 revealed to be most cytotoxic, also against all tested leukemia cell lines. The cell line SD‐1, however, was susceptible to all dendrimers. The mode of cell death was mainly determined by necrosis, especially at higher concentrations, while apoptosis played a subordinate role. The other dendrimers exerted no antimetabolic effects against LAMA‐84, K562, and SUP‐B15 cells. Therefore, these dendrimers are generally suitable as nontoxic drug carriers for leukemia cells. Abstract : Dendrimers are used for drug delivery. However, knowledge of their cell death‐inducing properties is essential. Therefore, a series of three poly(amido amine)‐derived and one poly(propylene imine) dendrimers was investigated for their cell‐growth inhibition of MCF‐7 and MDA‐MB‐231 breast cancer cells and for their antimetabolic effects against the LAMA‐84, K562, SD‐1, and SUP‐B15 leukemia cell lines. The cytotoxic representatives induced necrosis rather than apoptosis.